Are Rating Agencies Powerful? : An Investigation Into the Impact and Accuracy of Sovereign Ratings - Kiff, John (IMF Working Papers; Working Paper ;, 2012)
We find that Credit Rating Agencies (CRA)'s opinions have an impact in the cost of funding of sovereign issuers and consequently ratings are a concern for financial stability. While ratings produced by the major CRAs perform reasonably well when it comes to rank ordering default risk among sovereigns, there is evidence of rating stability failure during the recent global financial crisis. These failures suggest that ratings should incorporate the obligor's resilience to stress scenarios. The empirical evidence also supports: (i) reform initiatives to reduce the impact of CRAs' certification services; (ii) more stringent validation requirements for ratings if they are to be used in capital regulations; and (iii) more transparency with regard to the quantitative parameters used in the rating process.